2022
DOI: 10.1021/acsaelm.2c00681
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Wide-Range Triboelectric Sensor for Physiological Signal Monitoring and Human Motion Recognition

Abstract: Triboelectric nanogenerators, as a device that converts mechanical energy into electrical energy, can respond to external pressure stimuli. However, most triboelectric sensors can only perform pressure measurements in a narrow pressure range, which limits their application in multiple scenarios. Here, we proposed a wide-range triboelectric pressure sensor based on the difference in Young’s modulus of the materials and a double-sandwich-structure design. We analyzed the effect of the structural angle at the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 48 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…This device has an excellent range of pressure measurement of 0–450 kPa. 184 Meanwhile, the other performance parameters also are superior; for example, the sensitivity is 249.32 mV kPa −1 , the response time is 26 ms, and the detection limit is 8.72 Pa. Thus, this triboelectric pressure sensor can be used to detect small motion, and it can combine a convolutional gated recurrent unit model to recognize four human motions with 99.42% accuracy.…”
Section: Recent Advances Of Triboelectric Micro-pressure Sensors For ...mentioning
confidence: 93%
See 1 more Smart Citation
“…This device has an excellent range of pressure measurement of 0–450 kPa. 184 Meanwhile, the other performance parameters also are superior; for example, the sensitivity is 249.32 mV kPa −1 , the response time is 26 ms, and the detection limit is 8.72 Pa. Thus, this triboelectric pressure sensor can be used to detect small motion, and it can combine a convolutional gated recurrent unit model to recognize four human motions with 99.42% accuracy.…”
Section: Recent Advances Of Triboelectric Micro-pressure Sensors For ...mentioning
confidence: 93%
“…Some researchers are developing self-powered pressure sensors based on the triboelectric effect for motion monitoring. Kim et al reported a pressure sensor based on triboelectric- 181 2.2 V kPa −1 0.1-98 kPa Not known PDMS 182 3.627 kPa −1 0-8 kPa 5 Pa 1.264 kPa −1 8-80 kPa 5 Pa Porous PDMS 183 54.37 mV kPa −1 0-80 kPa Not known 9.80 mV kPa −1 80-240 kPa Not known PDMS 184 249.32 mV kPa −1 0-450 kPa 8.72 Pa PDMS/Ag 185 1.67 V kPa −1 0-3 kPa Not known 0.20 V kPa −1 3-32 kPa Not known PTFE-Nylon 176 1.33 V kPa −1 181 2.2 V kPa −1 0.1-98 kPa Not known Not known PDMS 182 3.627 kPa exoelectric nanogenerators for human motion monitoring, such as eye blinking, nger bending, knee bending and swallowing. 178 Because the device combines the triboelectric-exoelectric effect, it shows a higher sensitivity of up to 0.173 V kPa −1 .…”
Section: Motion Monitoringmentioning
confidence: 99%
“…In addition to the works discussed here, several interesting recent works have focused on the application of TENG-based self-powered sensors to human motion monitoring and biomechanical sensing. [167,168] Furthermore, research efforts have been channelized toward coupling environmentally sustainable and eco-friendly TENGs with custom-developed machine learning models for human motion prediction with a high degree of accuracy. [52] In addition to the applications of TENGs toward human motion monitoring, several research groups have focused on the structure and surface morphologies of triboelectric devices with the goal of optimizing their performance.…”
Section: Triboelectric Self-powered Sensorsmentioning
confidence: 99%
“…In addition, the sandwich structure has become the most mainstream method in the encapsulation of capacitive pressure sensors. The dielectric layer is prepared separately and the encapsulation electrode is directly superimposed. This packaging method is simple but easily introduces an air gap between the electrode and dielectric layer, resulting in a large difference in the performance of the sensor fabricated by each packaging. The above problems and consistency can be improved by docking the single electrode and dielectric layer as a whole.…”
Section: Introductionmentioning
confidence: 99%